ENVIRONMENTAL LAW ENFORCEMENT OF TOFU AND TEMPE WASTE DISPOSAL INTO THE SUBAK IRRIGATION IN JEMBRANA REGENCY - Ida Ayu Ima Purnama Sari; Ni Made Jaya Senastri; I Ketut Kasta Arya Wijaya (Sean Institute, 2023)
This study examines environmental law enforcement regarding the disposal of tofu and tempeh waste into subak irrigation in the Jembrana District. The purpose of this study was to analyze environmental law enforcements regarding the disposal of tofu and tempeh waste into the irrigation canal of the'Subak Kedua', Lelateng Village, Jembrana Regency and the efforts of the Environmental Service in preventing the disposal of tofu and tempeh waste into the 'Subak Kedua' irrigation, Lelateng Village, Jembrana Regency. This research is empirical legal research. The results of this study related to environmental law enforcement regarding the disposal of tofu and tempeh waste, law enforcement that have been carried out by civil service police unit and the Regional Regulation Enforcement Team according to applicable regulations, there has been a violation of Jembrana Regency Regional Regulation Number 5 of 2007 concerning Cleanliness and Public Order. After carrying out mediation, checking the location, calling, making statements, and giving warning letters from 1st to 3rd warning letters, the entrepreneur has followed up on the directions from the warning letters to create additional storage places for tofu and tempeh waste. As for the efforts of the Environmental Service in preventing the disposal of tofu and tempeh waste by conducting surveillance and monitoring of water quality regularly, cleaning up river waste to increase the ability of the self-purification process, namely the power of water to decompose pollutant substances that enter the river. Coaching was carried out for nine tofu and tempeh entrepreneurs to carry out business waste management before being discharged into waterways and for entrepreneurs to complete a business permit in the form of a Statement of Environmental Management, proposing to procure a Communal Water-waste Treatment Plant for water-waste management. In addition, the Environmental Service has routinely conducted outreach programs regarding environment protection and the dangers of waste.